THE COMPANY FUNDAMENTAL FACTORS AND SYSTEMATIC RISK IN INCREASING STOCK PRICE - Atika Jauharia Hatta; Bambang Sugeng Dwiyanto (Universitas Hayam Wuruk Perbanas, 2012)
Some factors in increasing stock price can be interesting when they are scrutinized. Whataffects the stock price so far has been the pursuit of any business recently. The research isaimed at identifying the effect of company fundamental factors (Earning per Share, PriceEarning Ratio, Debt to Equity Ratio, Current Ratio, Net Profit Margin, Dividend Payout Ratio,Return on Asset) to stock price and the extent of Beta (?) effect as measurement of systematicrisk in explaining the variance of prices in Indonesian Stock Exchange. Using regressionanalysis and McKinnon, White, and Davidson test (MWD test), the result found that thefunctional relational model is linier-log. According to the result of estimation to stock prices,it is discovered that EPS, PER, and HSM variables have positive and significant effects tostock prices, while DER and NPM variables have negative and significant effects. EPS is thedominant variable with strong relation to stock prices.